Batas Aurat Perempuan Saat Dipinang di Hadapan Laki-laki yang Meminangnya: Analisis Komparatif Pendekatan Jumhur Ulama dan Mazhab Zhahiriyah dalam Perspektif Ushul Fikih - Syamsurizal; Shifa Syahira (Journal of Social, Educational and Religious Studies, 2025)
This article comprehensively examines the differences in Islamic scholars' views regarding the limits of a woman's private parts during the proposal process in front of the man who proposes to her, with a comparative focus between the Jumhur Ulama and the Zahiriyah schools. This difference is rooted in the legal istinbath methodology used by each school in understanding the texts of the Qur'an and the hadith of the Prophet Muhammad. The Jumhur Ulama limit the permissibility of looking at the woman being proposed to the face and palms, while the Zahiriyah expands this permissibility to the entire body except for the major private parts. This research uses a qualitative-descriptive approach based on literature studies with ushul fiqh and comparative analysis. The results show that the differences in opinion are caused by differences in epistemological approaches in understanding the wording of the text, between the contextual and maqashid approaches and the literal-textual approach. This article emphasizes that the opinion of the Jumhur Ulama is stronger as a guideline because it is in line with the principles of sadd al-dzari'ah, maqashid al-shari'ah, and the social reality of contemporary Muslims.